Minutes of the 3rd Meeting of BRAC University Academic Council (AC) - Academic Council, BRAC University (Vice Chancellor's Office, BRAC University, 2013)
Minutes of the 3rd Meeting of BRAC University Academic Council, held on Monday, 18th March, 2002